Induction of total laparoscopic hysterectomy adopted the marionette technique in peri-menopausal and post-menopausal CIN3 patients-A retrospective observational study. - Prakash, Ved; Shalika (Student’s Journal of Health Research Africa, 2024)
Background A total laparoscopic hysterectomy (TLH) is a type of laparoscopic hysterectomy in which the trocars are used for all sutures, ligations, and surgical dissections including vaginal closure. This study intends to reveal the viability of TLH as a therapy option for perimenopausal and postmenopausal CIN3 patients at a single hospital over 4 years. Methods The analysis of medical records from approximately 44-year-old CIN3 patients who underwent open or laparoscopic hysterectomy at a tertiary care facility between 2017 and 2020 in a retrospective manner was done. Out of a total of 60 CIN3 patients, 10 were assigned to the ATH group and 50 to the TLH group. Results A total of 60 patients were selected, and they were divided into two groups based on the surgical technique: ATH (n = 10) and TLH (n = 50). The inclusion criteria comprised patients aged 44 years or older and/or those who had undergone an ATH or TLH. The TLH group experienced a shorter in-hospital stay (6 days vs. 10 days, p < 0.001) and perioperative blood loss (18 mL vs. 218 mL, p = 0.003) than the ATH group. Neither the operating length (153.40 ± 26.80 min vs. 160.0 ± 61.40 min, p = 0.825) nor age at hysterectomy (52 y vs. 76 y, p = 0.053) showed a significant difference between the two groups. Conclusion For perimenopausal and postmenopausal CIN3 patients, hysterectomy is a suitable therapeutic option, albeit being more intrusive than conization. Due to its less invasive nature, a total laparoscopic hysterectomy with marionette approach may be a better option in these situations. Recommendations It is advised that clinicians regard TLH as the optimal surgical choice for perimenopausal and postmenopausal CIN3 patients, owing to its minimally invasive characteristics, diminished complications, and expedited recovery period.